2022
DOI: 10.3390/polym14020344
|View full text |Cite
|
Sign up to set email alerts
|

DNA/Magnetic Nanoparticles Composite to Attenuate Glass Surface Nanotopography for Enhanced Mesenchymal Stem Cell Differentiation

Abstract: Mesenchymal stem cells (MSCs) have extensive pluripotent potential to differentiate into various cell types, and thus they are an important tool for regenerative medicine and biomedical research. In this work, the differentiation of hTERT-transduced adipose-derived MSCs (hMSCs) into chondrocytes, adipocytes and osteoblasts on substrates with nanotopography generated by magnetic iron oxide nanoparticles (MNPs) and DNA was investigated. Citrate-stabilized MNPs were synthesized by the chemical co-precipitation me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 106 publications
(118 reference statements)
0
10
0
Order By: Relevance
“…The studies conducted in this regard are not limited to BMSC differentiation. For instance, Ishmukhametov et al studied differentiation of adipose-derived MSCs (hMSCs) into chondrocytes, adipocytes and osteoblasts on DNA/Magnetic nanocomposites [ 186 ].…”
Section: Tissue Engineering Applications Of Fe 2 O...mentioning
confidence: 99%
“…The studies conducted in this regard are not limited to BMSC differentiation. For instance, Ishmukhametov et al studied differentiation of adipose-derived MSCs (hMSCs) into chondrocytes, adipocytes and osteoblasts on DNA/Magnetic nanocomposites [ 186 ].…”
Section: Tissue Engineering Applications Of Fe 2 O...mentioning
confidence: 99%
“…In addition, MSCs and fibroblasts have been identified as appropriate mechanical stimulatory parameters for regulating proliferation [ 28 ]. In the aspect of differentiation potential, accumulating evidence have shown that the mechanical microenvironments including stiffness and tension influence the osteogenic- and adipogenic-differentiation of ASCs [ 47 , 48 , 49 ]. In addition to the level of mechanical stress, rate of stress relaxation is also identified as the regulator of differentiation of MSCs [ 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…A lot of efforts to regulate stem cells, particularly by various biomaterials and their nano-architected structures, have been made. Recent studies have shown that advances in the biomaterial- and nano-technologies can provide the temporal and narrow-range of mechanical signal control to regulate ASC fate and behavior [ 42 , 48 , 61 , 62 ], which make it possible to establish more appropriate procedure to apply to the clinic investigation. Thus, the application of specific physical factors can propel the specific phenotype of ASCs potentials in more clinically favorable and specialized direction.…”
Section: Resultsmentioning
confidence: 99%
“…So far, the effects of various materials and structures on stem cells have been extensively studied [ 114 , 115 ]. Magnetic nanoarchitectonic materials are used to guide the stem cell differentiation [ 116 , 117 ] and multicellular 3D spheroids [ 118 ]. Those studies will be the cornerstone of nanoarchitectonics using stem cells.…”
Section: Introductionmentioning
confidence: 99%